A Study of Writing and Teaching Skills in Students and Teachers: The Importance of Developing Writing and Teaching Skills (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Writing and teaching is knowledge and must be learned like other skills. Most individuals takewriting for granted, despite its importance in many contexts, such as the communication of ideas,instructions, and legal agreements. Writing effectively involves so much more than just using the rightwords and syntax. Among the many applications of the written word are the transmission of knowledgeand the preservation of culture. It serves several crucial purposes in a person's everyday life, from theprofessional to the academic to the scholarly to the medial to the social and the personal. Writing is theprimary method of conducting official business. Writing's primary function is obviously documentation,especially given the contrast between writing's durability and that of speech. Official and legal records,typically in written form, are archived for future reference. Only in paper can lawyers properly referenceprior rulings and statutes. There is no way to conceive of a world without these records, which includedocuments, books, journals, notes, instructions, bills, and letters. Students frequently use writtenclassroom activities such as note taking, task and assignment recording, problem solving, drafting, andmaking observations. For professional or educational reasons, an increasing number of peoplerecognize the importance of developing their written English skills. A literate person may only participatefully in society if they themselves are literate hence reading is fundamental to the development of anycivilization. According to Bacon, a fully realized human being is one who can read, conduct aconference, and put pen to paper. Learning the language itself is insufficient. In a given region, nativesare expected to acquire the language spoken there, but literacy is not a need for education.